The oxygenating constituent of 3, 6‐diketocamphane monooxygenase from the CAM plasmid of Pseudomonas putida: the first crystal structure of a type II Baeyer–Villiger monooxygenase. Corrigendum. Issue 4 (12th April 2018) - Isupov, Michail N.; Schröder, Ewald; Gibson, Robert P.; Beecher, Jean; Donadio, Giuliana; Saneei, Vahid; Dcunha, Stephlina A.; McGhie, Emma J.; Sayer, Christopher; Davenport, Colin F.; Lau, Peter C. K.; Hasegawa, Yoshie; et al.
Abstract : The article byIsupov et al. [(2015). Acta Cryst. D71, 2344–2353] is corrected. Abstract : A statement is amended in the article byIsupov et al. [(2015 ). Acta Cryst. D71, 2344–2353] .